Nitrate Leaching in Soils Treated With Activated Sludge, Cattle Manure and Chemical Fertilizers - Mostofi, Nooshin (2009)
Nitrogen fertilizers have been recognized as an important factor in crop’s yield level, however more application of N fertilizers in the soil have some adverse effects on environment and especially on ground water contamination. Perception and recognition the factors influencing nitrate transport through soil profile is helpful for fertilizer management to minimize adverse impacts on environment and nitrate leaching below the root zone. In this study, 15 large cylindrical lysimeters with 1 m height and 0.56 m diameter were filled with clay and sandy loam soil and planted with maize to investigate nitrate leaching under different types of N-fertilizer; activated sludge (20 ton/ha), cattle manure (40 ton/ha) and chemical fertilizer (containing 70 kg N/ha). Also 3 lysimeters with 1.4 m height were used to investigate the effect of soil depth in nitrate leaching in sandy loam soil. Totally the study involved nine treatments. Nitrate concentrations in the soil and drainage water samples were analyzed by spectrophotometer method and nitrate mass were calculated in irrigation water, soil and drainage water. Crop production for different treatments has been compared too. The nitrate-N concentrations were higher than 10 mg N/L (the maximum acceptable concentration) in 60% of the observations for OFcl. The Nitrate-N concentrations were higher than 10 mg N/L in 48 and 51% of the samplings for the CFcl and OFcl treatments, respectively. The Nitrate-N concentrations were almost always lesser than 10 mg/L in the lysimeters containing sandy loam soil. Results illustrate nitrate leaching from activated sludge and organic fertilizer in clay loam soil was significantly greater than the other treatments (110 kg/ha and 229 kg/ha respectively). Among all treatments of this study organic manure in clay loam soil had the greatest nitrate accumulation in soil (15.17 mg/kg) and chemical fertilizer in sandy loam soil had the least (8.56 mg/kg). Experimental results also showed that manure application could result in NO3 --N accumulation increase in the deeper soil profiles compared with mineral fertilization and activated sludge. The results demonstrate that nitrate, from the activated sludge and chemical fertilizers, transported through the soil profile is more than the organic manure after the 75 cm depth, and the accumulation of organic fertilizer is mostly 60 to 90 cm depth from the soil surface.